2021
DOI: 10.1093/eurjcn/zvab048
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in elderly inpatients with cardiovascular disease: an exploration of associated factors

Abstract: Aims Older patients with cardiovascular diseases (CVDs) are more likely to develop frailty. Few studies have investigated frailty status, and its multiple associated factors, in this population. The aim of the present study was to explore frailty status, and its multidimensional associated factors, in elderly inpatients with CVDs. Methods and results In this cross-sectional study, 1021 inpatients with CVDs aged ≥60 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Our nding was consistent with the studies conducted by He et al and Meng et al [34,35], indicating that age was a signi cant factor associated with frailty in patients with CHF. A systematic review supported this, revealing that older patients with HF were six to seven times more likely to be frail than non-frail individuals [36].…”
Section: Discussionsupporting
confidence: 93%
“…Our nding was consistent with the studies conducted by He et al and Meng et al [34,35], indicating that age was a signi cant factor associated with frailty in patients with CHF. A systematic review supported this, revealing that older patients with HF were six to seven times more likely to be frail than non-frail individuals [36].…”
Section: Discussionsupporting
confidence: 93%
“…Frailty is also a common clinical indicator of poor prognosis in the elderly and a bidirectional causal relationship between them is probable. The incidence of frailty in elderly Chinese individuals is thought to range from 9.9% to 31.92% and pre-frailty from 33.9–39.62% [ 23 25 ]. Elsewhere, studies have reported frailty and pre-frailty rates to be 16%-94% and 38%-87.8%, respectively, among geriatric patients [ 4 , 13 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diseases included were CVD due to atherosclerosis, that is, ischemic heart disease or coronary artery disease, and other CVDs, that is, hypertension, congenital heart disease, rheumatic heart disease, cardiomyopathy, and arrhythmia. [ 18 ] The specific inclusion criteria were: Age ≥ 60 years; Self-care ability; and Informed consent to participate in this study. The exclusion criteria were: Day surgery patients; < 2 Types of drugs prescribed at discharge; Transferred patients; Patients discharged voluntarily; Patients who died during hospitalization; Patients with mental disorders or inability to communicate; Patients who died during the follow-up period after discharge; and Patients who were followed up for 2 consecutive days and those who did not respond to telephone after 3 attempts.…”
Section: Objects and Methodsmentioning
confidence: 99%